2019
DOI: 10.1111/jar.12651
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas and legal aspects in contraceptive counselling for women with intellectual disability—Focus group interviews among midwives in Sweden

Abstract: Background Few studies have explored ethical and legal issues in contraceptive counselling among women with intellectual disability (ID). This study aimed to gain a deeper understanding of these issues during midwifery contraceptive counselling. Method The present authors interviewed 19 midwives in five focus groups in Sweden 2016 – 2017 and analysed data with content analysis. Results The participants expressed that women with intellectual disability have equal right to relationships and sexual expressions, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…Ensuring privacy and respecting a person's autonomy while at the same time protecting them from harm was another balance described by the participants. This dilemma was also described by midwives in relation to contraceptive counselling for women with ID [13,25]. In addition to their own strategies, the participants had several suggestions for improvement such as a clear mandate, improved interprofessional collaboration and supporting policies and guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring privacy and respecting a person's autonomy while at the same time protecting them from harm was another balance described by the participants. This dilemma was also described by midwives in relation to contraceptive counselling for women with ID [13,25]. In addition to their own strategies, the participants had several suggestions for improvement such as a clear mandate, improved interprofessional collaboration and supporting policies and guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Four further records were identified through the main author's manual search of key journals and Google Scholar, leading to a total of 17 articles. Further review of the 17 articles identified revealed that two of the selected papers [27,28], were separate publications originating from the same primary research. Although these had a somewhat different focus, a review of their content indicated that there was a significant degree of overlap.…”
Section: Screening Processmentioning
confidence: 99%
“…Although these had a somewhat different focus, a review of their content indicated that there was a significant degree of overlap. As one of these two articles [27] provided a richer description of concepts represented in both studies, a decision was made to retain only that article.…”
Section: Screening Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside non-existent guidelines about counselling women with ID, there is uncertainty about what optimal care is. The biases and ethical dilemmas experienced by midwives on providing contraceptive counselling is little researched and that is the focus of this study by Höglund and Larsson 3…”
Section: Contextmentioning
confidence: 99%